The Influence of Overconfidence Bias and Digital Literacy on Decision-Making Quality Among Digital Business Practitioners - Jessica Kaligis; Audika Briantari Briantari Zaen (International Journal Of Humanities Education and Social Sciences (IJHESS), 2026)
This study aims to analyze the influence of Overconfidence Bias and Digital Literacy on Quality DecisionMaking among digital business actors. The research employed a quantitative approach. Data were collectedthrough an online questionnaire distributed to 144 digital business actors, including marketplace sellers, onlineshop owners, resellers, dropshippers, and digital-based MSMEs. The research instrument consisted of 13 Likert-scale items adapted from previous studies. Data were analyzed using the Partial Least SquaresStructural Equation Modeling (PLS-SEM) method with SmartPLS 3 software. The results indicate thatOverconfidence Bias has a negative and significant effect on Quality Decision Making, while Digital Literacyhas a positive and significant effect on Quality Decision Making. Furthermore, Digital Literacy demonstrates a more dominant influence than Overconfidence Bias in explaining decision-making quality. These findingssuggest that enhancing digital literacy and controlling cognitive biases are crucial factors in producing morerational, objective, and high-quality business decisions in the digital era. Keywords: Overconfidence Bias, Digital Literacy, Quality Decision Making, Digital Business Practitioners;